Regional Economic Outlook, April 2018, Asia Pacific : Good Times, Uncertain Times: A Time to Prepare. (Regional Economic Outlook, 2018)
Asia is expected to grow by about 5 1\2 percent this year, accounting for nearly two-thirds of global growth, and the region remains the world's most dynamic by a considerable margin. But despite the strong outlook, policymakers must remain vigilant. While risks around the forecast are broadly balanced for now, they are skewed firmly to the downside over the medium term. Key risks include those of further market corrections-possibly triggered by inflation surprises and/or faster-than-expected monetary tightening in advanced economies-a shift toward protectionist policies, and an increase in geopolitical tensions.